Sensitivity of simulated microphysics to the raindrop distribution shape parameter and comparisons with observations - Van Valkenburg, Kristen, author; van den Heever, Susan, advisor; Rutledge, Steven, advisor; Dolan, Brenda, committee member; Eykholt, Richard, committee member (Colorado State University. Libraries, 2022)
Representation of precipitation microphysics remains a challenge in numerical modeling. Model simulations using two-moment bulk microphysics require a priori choices, such as the rain size distribution shape parameter (ν), which is used to determine the width of the rain drop size distribution (DSD). Selection of ν is often somewhat arbitrary being due, in part, to a lack of observations on which to base such decisions. In this study, the sensitivity of rainfall characteristics to ν is assessed using numerical model simulations and compared with an observational data set. A continental deep convection (CD) case and a shallow maritime (MS) case are simulated using bin and bulk microphysical parameterizations. The model results show that accumulated precipitation in the MS case decreases 385% with increasing v, while the CD case shows minimal variability. In the CD case, where both warm-, mixed-, and ice-phase microphysical processes are occurring, graupel mixing ratios and number concentrations show a monotonic decrease with increasing ν, while hail mixing ratios and number concentrations show a monotonic increase with increasing ν. An analysis of the microphysical processes comprising the rain budget reveals the MS case shows a shifting balance between evaporation and cloud water collection with changes in ν, with increasing evaporation being the predominant influence on decreased surface precipitation. In the CD case there is notable variability in a variety of microphysical processes including important feedbacks to ice species. Cloud water collection and evaporation are the greatest contributor in the CD simulations with lower rain shape parameters. The value of ν greatly impacts contributions to the rain via melting of ice hydrometeors. As the value of ν increases, melting of ice species by collisions with rain decreases, and is near zero in the ν=10 simulation. Also, as ν increases, the rates of hail melting into rain increases. This analysis allows us to gain perspective into how the assumed rain n in bulk microphysics parameterizations impacts both warm rain processes and feeds back onto mixed-phase and ice-phase processes. In addition to the bulk parameterization sensitivity tests, both cases are also simulated using a bin microphysics scheme, where the hydrometeor size distributions are allowed to freely evolve throughout the simulation. Using appropriate fitting approaches, we evaluate the range of rain shape parameters predicted in both cases as well as the variability of ν values throughout the three-dimensional storm structure. The microphysical processes and rainfall characteristics of the bulk simulations are also evaluated relative to disdrometer observations using a previously developed 2D phase space of the intercept parameter (logNw) and median drop diameter (D0). In this framework, lower ν values in the bulk microphysics MS case correspond more closely with observations, while in the CD case, higher ν correspond more closely with observations. These findings demonstrate the sensitivity of those assumptions constraining rain DSDs in microphysical parameterizations and provide a model-to-observation comparisons to help guide a priori choices of ν necessary for more accurate simulations utilizing bulk microphysics schemes.
Keywords: observations; drop size distribution; shape parameter